Beyond Positive Law: Women’s Condition and Role within the Patriarchal Structure (Trento Student Law Review, 2025)
Women’s suffering and resistance within the well-known patriarchal structure have existed since time immemorial. This will be demonstrated by starting from the concept of the victim from a broader perspective, touching on its meaning, the prejudices related to it, and the difficulties encountered by victims within the adversarial justice system, finally concluding with the need to seek help and the related challenges.An example of a victim is surely the woman within the above-mentioned structure, mainly because of the roles she is forced to perform. It is difficult for her to be coerced into being a virgin, which is a hurtful anatomical myth and a cage. Even more demanding is the role of motherhood, which is a source of joy for some, yet a burden. While maternity might be fulfilling, it still exposes women to significant physical, psychological, and social disadvantages. Enjoyment does not erase the structural costs imposed on women’s bodies and lives. Finally, what most call “sex work” – but is indeed brutal, non-consensual sex, thus rape – will be examined, and the legislative models used to regulate or tackle it will be considered, together with some unpopular critiques of the prostitution debate.
Keywords: Victim; Virginity; Motherhood; Prostitution; Prison System